Oospila bulava, a new emerald geometrid moth from South America (Lepidoptera, Geometridae, Geometrinae) - Lindt, Aare; Viidalepp, Jaan (Zootaxa, 2015)
Warren (1897) described the genus Oospila for Phorodesma trilunaria Guenée, 1857 from Brazil. Prout (1912; 1932–1933) revised the genus, listing 48 species in the first publication and 58 species in the latter one, in Oospila. Cook and Scoble (1995) grouped eight related genera under Oospila, including 73 species and dividing these into 13 species groups. Pitkin (1996) relied on this revision while publishing a monographic review of the Neotropical geometrine genera. Parsons et al. (1999) attributed the same species that in Cook and Scoble (1995) to the genus. Two species are described later (Viidalepp, 2002; Lévèque & Viidalepp, 2015). While revising collections from the Neotropical region during the last decade, the authors of the present article have found several undescribed taxa: cryptic species are frequently overlooked in large-scale works (Vodă et al., 2014). The result of one case study is published in this article. The primary and subsequent descriptions of relevant taxa are consulted.